The structural analysis of key indicators of Turkish Manufacturing Industry: ORESTE and MAPPAC applications - (:unkn) unknown (My University, 2011)
This work presents the results obtained from an attempt for multi-criteria analysis of the economic activity in 2007 for Turkish Manufacturing Industry. In analysis of the economic activities of manufactoring Industry, five macro-economic criteria have been considered. These are; Share in Total Production, Economic Controbution, Share in Total Exports, Export Orientation and Share in Total Employment. All of the Turkish Manufacturing Industry was analyzed and sorted under the five criteria by means of ORESTE and MAPPAC methods. © EuroJournals Publishing, Inc. 2011.
Keywords: Multi-criteria decision analysis; ORESTE and MAPPAC; Turkish Manufacturing Industry